1942
DOI: 10.1021/i560111a012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphate for Separation of Cobalt from Iron

Abstract: EDITION 859 producibility, because ammonium ions have a pronounced effect on the final color. For the same reason, sulfates were chosen in preference to chlorides.The colorimeter can be read to Vs scale division. Table I indicates that reproducible results can be obtained with only approximate measurement of the volumes of reagents used. Duplicate determinations indicate the same limit of reproducibility which, from the slope of the line in Figure 1, may be seen to correspond to 0.06 mg. of cobalt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1949
1949
1953
1953

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…North and Wells (226) found that disodium hydrogen phosphate in basic acetate medium at pH 3.5 produced a better separation of iron from cobalt than ammonium hydroxide alone. Davidson (72) reported that a boiling solution containing 50% ethanol produced ferric hydroxide which was readily filtered and washed.…”
Section: Ironmentioning
confidence: 99%
“…North and Wells (226) found that disodium hydrogen phosphate in basic acetate medium at pH 3.5 produced a better separation of iron from cobalt than ammonium hydroxide alone. Davidson (72) reported that a boiling solution containing 50% ethanol produced ferric hydroxide which was readily filtered and washed.…”
Section: Ironmentioning
confidence: 99%